1993
DOI: 10.1007/bf00049030
|View full text |Cite
|
Sign up to set email alerts
|

The role of herbivores in the collapse of the Gracilaria resource at Saldanha Bay, South Africa

Abstract: At Saldanha bay on the west coast of South Africa, annual yields of beach-cast Gracilaria often exceeded 1000 metric tons, until the construction of an ore jetty and breakwater in 1974. Yields were then drastically reduced, recovered to 429 tons in 1988, then fell to zero. Diving surveys revealed a steady decline in the biomass of the remaining beds from 50 t in April to less than 1 t in August 1989. The presence of large numbers of herbivores suggested that grazing was the cause. This hypothesis was tested by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

1995
1995
2008
2008

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 10 publications
1
3
0
Order By: Relevance
“…Anderson et al (1993) found Gracilaria only in the northern part of Small Bay in Saldanha Bay, which corresponds well to findings in this study and that of Isaac (1956) even before the construction and dredging was done in the bay. In 1989, the total biomass, in Small Bay, was estimated at 523 tons in May, 122 tons in June, 15 tons in August and 0.6 tons in October (all fresh weight) (Anderson et al 1993) as the effects of grazers became apparent. This study estimated the standing stock at 538 tons fresh weight, an amount very similar to the May 1989 estimate.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…Anderson et al (1993) found Gracilaria only in the northern part of Small Bay in Saldanha Bay, which corresponds well to findings in this study and that of Isaac (1956) even before the construction and dredging was done in the bay. In 1989, the total biomass, in Small Bay, was estimated at 523 tons in May, 122 tons in June, 15 tons in August and 0.6 tons in October (all fresh weight) (Anderson et al 1993) as the effects of grazers became apparent. This study estimated the standing stock at 538 tons fresh weight, an amount very similar to the May 1989 estimate.…”
Section: Discussionsupporting
confidence: 92%
“…The low returns over the last 20 years indicate that the gracilarioid stocks have not yet recovered to the levels before the construction of the iron ore jetty and breakwater in Saldanha Bay in 1974. Although the construction and dredging are considered to have played a major role in the initial collapse of the gracilarioid stocks, the subsequent collapse in the late 1980s and early 1990s in Saldanha Bay has been ascribed, by Anderson et al (1993), to grazing by herbivorous fish, keyhole limpets and urchins. Smit et al (2003) have also shown that grazing of the isopod Paridotea reticulata can have a significant effect on the biomass of Gracilaria gracilis in tank culture.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations